Proses Pembuatan Mesin Pencacah Polimer Komposit Kapasitas 10 kg/Jam - Lubis, Rahmat Pande Raja; Iswandi, Iswandi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The problem of plastic waste continues to increase and requires effective technical solutions through the recycling process. One of the crucial stages is enumeration, which aims to reduce the size of the material so that it can be easily reprocessed. This research aimed to design a plastic and composite polymer shredding machine with a capacity of 10 kg/h, featuring a simple construction, energy-saving capabilities, and suitability for both household and small industrial applications. The design process includes power requirement analysis, frame design, blade selection, and transmission system. The test results showed that the machine was able to produce plastic shreds of an average size of 5 mm with performance close to the target capacity. This machine has the potential to improve the treatment of plastic waste locally.